The Coproduction illusion: considering the relative success rates and efficiency rates of securing an Education, Health and Care plan when requested by families or education professionals. Issue 2 (29th September 2021) - Boddison, Adam; Soan, Sue
Abstract : This comparative study examines success and efficiency rates for Education, Health and Care (EHC) needs assessments in England when requested by families or education professionals. England is the only nation in the UK with EHC needs assessments. These are requested from the Local Authority (LA) if the school's ordinarily‐available provision is insufficient for individuals to make expected progress. Policy states that needs assessments should include parents, pupils and professionals in all decision making (coproduction). After a needs assessment, the LA may issue an EHC plan. This study considers whether the outcome of a needs assessment (issuing an EHC plan) is independent of the source of the request. Statistical analysis compared outcomes of needs assessments requested by families and education professionals. Analysis of publicly‐available datasets and policy provided further context. Findings included: (i) a need for further research to explore inconsistencies in outcomes of needs assessments across England; (ii) LAs efficient at issuing EHC plans were consistently efficient for requests from education professionals and families; (iii) a potential discrepancy between families' perceived level of involvement and the reality: a 'coproduction illusion'. It is proposed that policy and guidance in England requires revision to ensure consistent use of language, roles, and responsibilities.